MANAJEMEN MUTU PEMBELAJARAN DALAM MENINGKATAKAN HASIL BELAJAR SISWA DI MTS ANWARUL FALAH CIKARANG UTARA, KABUPATEN BEKASI - Afaf Ali Abdullah; Farizal MS; EE Junaedi Sastradiharja (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2022)
This study aims to describe the implementation of learning quality management in improving the quality of student learning outcomes, and to find out how the role of teachers in improving the quality of student learning outcomes at MTS Anwarul Falah and how student learning outcomes at Mts. Anwarul Falah, Bekasi Regency. This study uses a qualitative approach with the method used in this study is descriptive research. Collecting data using interviews, study documentation and observation. The main informants in this study were the Head of Madrasah and other informants were teachers and students as well as students' guardians. The results of the research are that the Anwarul Falah Madrasah has carried out the stages of learning quality management that has been carried out by the teacher, but the Anwarul Falah Madrasah does not have quality tools or quality guidelines so that the implementation of quality improvement management has not followed the principles of quality management. Even teachers in teaching are still not varied and rely on existing facilities in schools. The student learning outcomes at Anwarul Falah are sufficient to meet the minimum completeness criteria (KKM).